EFL Learners’ Experiences in Using Tiktok to Enhance Pronunciation and Speaking Fluency - Siregar, Prima Yanti; Heridayani, Heridayani; Siregar, Nurmaliana Sari; Wariyati, Wariyati; Ani, Fitri (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
This study explores how English as a Foreign Language (EFL) learners use TikTok to improve their pronunciation and speaking fluency. Recognizing the growing influence of social media in education, the research investigates the ways in which students integrate TikTok into their language learning practices. A descriptive qualitative design was employed to capture students’ lived experiences. Nine undergraduate students from AMIK ITMI Medan participated in semi-structured interviews and shared their TikTok-based speaking activities. Data were analyzed thematically to identify recurring patterns and insights. The findings reveal that TikTok serves as a practical and engaging tool for developing oral skills. Students used short video features to imitate native speakers, repeat expressions, and refine their pronunciation through multiple recordings. The process also improved their fluency as repeated performance reduced hesitation and increased speech confidence. Moreover, the platform’s interactive and entertaining nature fostered motivation, enjoyment, and a sense of achievement. Despite these benefits, some challenges were noted, including distractions from non-academic content, the use of informal language, and technical barriers. In conclusion, the study demonstrates that TikTok can function as an effective supplementary platform for EFL speaking practice. It provides authentic exposure, encourages self-directed learning, and enhances motivation in a low-pressure environment. The results suggest that teachers should guide students in purposeful use of TikTok, balancing creativity with structured learning objectives to maximize its pedagogical value.